Development of an assessment tool for team integration in alliance projects. Issue 4 (7th September 2015) - Che Ibrahim, Che Khairil Izam; Costello, Seosamh B.; Wilkinson, Suzanne
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to report on a doctoral thesis that developed an Alliance Team Integration Performance Index (ATIPI), an assessment tool for measuring team integration performance in alliance projects. It provides a summary of the thesis findings, shares the candidate's doctoral journey and discusses both the thesis "with publication" format and the doctoral programme at the University of Auckland. Design/methodology/approach – This study employed a qualitative and quantitative research methodology (mixed methods research). Research methods applied as reported in this thesis include the Delphi questionnaire survey, interviews and empirical questionnaire surveys with the alliance experts involved in road infrastructure projects. Findings – Results from the thesis indicate that the ATIPI is characterized by three elements: first, the most significant Key Indicators (KIs), signifying their dominant influence; second, the suitable quantitative measures for each of the KIs, to promote objective assessment over time; and third, the performance-level boundaries for each KI, to reduce the subjectivity of assessment and promote consistency. The assessment tool was found to be both practical and applicable based on a validation interview and subsequent testing with alliance experts on real life alliance infrastructure projects. Practical implications – As team integration is the central tenet of alliance projects, the ATIPI is an ideal assessment tool to facilitate the measurement of team integration performance consistently and objectively over the life cycle of alliance projects. Also, the ATIPI is expected to make a fundamental and positive difference towards improving the integration practice of alliance teams. Originality/value – This study extends the team integration literature by providing significant insights into the practical evaluation of team integration performance, specifically in alliance projects.